STUDI AWAL RESIKO GESTASIONAL DIABETIK MELITUS DI WILAYAH KERJA PUSKESMAS BOJONG I KEBUPATEN PEKALONGAN - Isyti'aroh Isyti'aroh; Sugiharto Sugiharto; Siti Rofiqoh; Windha Widyastuti (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2023)
AbstracGestational Diabetes Mellitus (GDM) is one of the complications of pregnancy that increases the morbidity and mortality of both the mother and the baby. This study aims to determine the risk factors that exist in all pregnant women in the working area of the Bojong I Public Health Center in Pekalongan. Study design used cross sectional. Sampling was taken using the total sampling technique for the entire population of pregnant women whose number was known, namely 146. The research location was in the working area of the Bojong 1 Public Health Center, Pekalongan Regency, which covering 14 villages. The research instrument used a questionnaire containing questions about risk factors for GDM including age, parity, body mass index before pregnancy, history of GDM, history of increased blood sugar, history of polycystic ovary syndrome, history of giving birth to babies > 4 kg, family history of DM, history of exercise routine before pregnancy, history of stillbirth, history of pregnancy with more than 1 fetus and history of babies born with congenital defects. The results showed that multiparity was the most common risk factor found in 106 (72.6%). Cumulatively, the majority of respondents only had one risk factor, namely 73 (50%). The conclusion from the study is multiparity is the most risk factor for GDM.